If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = y + -25 Reorder the terms: -16 = -25 + y Solving -16 = -25 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -16 + -1y = -25 + y + -1y Combine like terms: y + -1y = 0 -16 + -1y = -25 + 0 -16 + -1y = -25 Add '16' to each side of the equation. -16 + 16 + -1y = -25 + 16 Combine like terms: -16 + 16 = 0 0 + -1y = -25 + 16 -1y = -25 + 16 Combine like terms: -25 + 16 = -9 -1y = -9 Divide each side by '-1'. y = 9 Simplifying y = 9
| 4y+11y=120 | | 102-6x=12x+20 | | [2x-3]=6 | | 28-k=-19 | | k-49=-62 | | 13-7x=88-42x | | (x)(6)=-30 | | 19-2x=5-10x | | -14t+7=49 | | -11.1x=77.7 | | 4x-f=-22 | | x-8.1=-3.7 | | -9(3b+2)+(28b-2)=0 | | -5-4+q=12 | | p^3+7p-6=0 | | 4s^2+8s=221 | | 5.3q-1.7-5.5q=-1.29-3.6 | | 2611x+622=126 | | 6y-15=y | | 23=3y+5 | | 223-5x=40x+18 | | 7y=3y+8 | | 11+x=5 | | 11.7=w+16.8 | | x-47=-46 | | 4(x+7)=50 | | 126-3x=33x+22 | | 100x-5=90x | | 4a+2a=6a | | 2x+5=35-4x | | 14b-24=-2b+8 | | 9-10x=66-31x |